68.2k views
5 votes
Select whether the equation has a solution or not.



√(x + 1) = 7 - 2 √(x)
x+ 1 = 7 - 2√2
roots​

User Jjsantoso
by
4.8k points

1 Answer

3 votes

Answer: The equation has a solution .

Explanation:

Since we have given that


√(x+1)=7-2√(x)

Squaring on both the sides, we get that,


x+1=(7-2√(x))^2\\\\x+1=49+4x-28√(x)\\\\3x+48-28√(x)=0

Let
√(x)=y\implies x=y^2

So, our equation becomes,


3y^2-28y+48=0\\\\y=(14)/(3)\pm (2√(13))/(3)\\\\√(x)=(14)/(3)\pm (2√(13))/(3)\\\\x=((14)/(3)\pm (2√(13))/(3))^2

So,
x=(248)/(9)\pm (56√(13))/(9)

Hence, the equation has a solution .

User JPCosta
by
4.1k points